Good morning, chick - Ginsburg, Mirra; Barton, Byron; Chukovskini, Korneni 1882-1969. (New York Greenwillow Books, 1980)
When he tries to imitate a rooster, a newly-hatched chick falls in a puddle.
Keywords: Chickens -- Fiction